An analytical cross-sectional study on optimal (timely or cumulative age-appropriate) routine childhood immunization coverage in the communities of Ebonyi state, Nigeria - Ugwu I. Omale; Cordis O. Ikegwuonu; Glory E. Nkwo; Chimaobi C. Iwegbulam; Louisa C. Ekwuazi; Chidinma I. Amuzie; Richard L. Ewah (Scientific Reports)
Abstract Optimal (timely or cumulative age-appropriate) routine childhood immunization coverage (the receipt of every recommended vaccine dose at the recommended age and time-interval between doses) will enhance optimal protection against vaccine-preventable infectious diseases (VPDs) which have been causing significant morbidity and mortality and recurring outbreaks among children younger than five years. This study evaluated optimal routine childhood immunization coverage, and the predictors, in Ebonyi state, Nigeria. This study was a baseline cross-sectional household survey within a cluster-randomised controlled trial and was conducted from July 2 to 16, 2022 among consenting mother–child pairs, in which the children were aged 5–23 months (subdivided into 5–11 and 12–23 months), in 16 randomly selected geographical clusters where the primary health care (PHC) facilities were providing maternal and child health care services including weekly routine childhood immunization. Data was collected using structured interviewer-administered questionnaire in KoBoCollect in android devices. Vaccination data was collected from the vaccination cards of the children. Descriptive analysis and multivariate generalized estimating equations were carried out. Of 1262 children aged 5–11 months, 8.6% had optimal (timely or cumulative age-appropriate) receipt of every recommended birth to 14 weeks vaccine (this was 18.3% of the 596 who had received every recommended vaccine dose) and the median (IQR) receipt timeliness (age-appropriate vaccines receipt) score for the recommended birth to 14 weeks vaccines by these children was 79.3 (64.9–91.7). Of 1166 children aged 12–23 months, 2.9% had optimal receipt of every recommended birth to nine months vaccine (this was 10.6% of the 320 who had received every recommended vaccine dose) and the median receipt timeliness score for the recommended birth to nine months vaccines was 65.0 (45.8–84.4). The most significant predictor of optimal (timely or cumulative age-appropriate) routine childhood immunization coverage of every recommended vaccine was decrease in the travel time to immunization facility. Other predictors were having a mother who completed secondary or higher education, delivery at a health facility, decrease in the age of the husband of the mother, decrease in the birth order of the child, and urban/semi-urban residence. The evidence calls for policy actions and interventions to increase optimal routine childhood immunization coverage, and indicate specific factors to be considered, in the efforts to tackle the recurring outbreaks of VPDs.